Diritti e pratiche della maternità al tempo dell’emergenza Covid-19. Sradicamento e riconfigurazione del parto tra Pantelleria e Trapani - Boiano, Ilaria; Buffon, Veronica; Cecchini, Cristina Laura (Antropologia Pubblica, 2024)
At the beginning of March 2020, the maternity unit at the local hospital (punto nascita) situated on the island of Pantelleria was closed by the State authority. Local pregnant women were forced to move at their own expense from the little island to Trapani (Sicily), for an indefinite period of time while waiting for their children to be born. Following this closure, a group of local women decided to promote civic protests denouncing the effects of the closure of the punto nascita. In this article, we combine legal and anthropological approaches to examine the international regulatory framework of sexual and reproductive health and the legislative reforms which have led to the progressive erosion of health services for women from Pantelleria. Yet, we offer a primary reflection on the collective and political responses articulated and enacted by he women from the island in response to the suspension of the maternal health care services. In conclusion, as a result of the dialogue and cooperation among the lawyers, the anthropologist and the civil society on possible future actions promoting women’s health rights, a map of the envisioned transformative strategies and potential strategic litigation will be presented with reference to the gender and feminist perspective.